Preclinical characterization of [18F]T-008, a novel PET imaging radioligand for cholesterol 24-hydroxylase - Koike, Tatsuki; Constantinescu, Cristian C.; Ikeda, Shuhei; Nishi, Toshiya; Sunahara, Eiji; Miyamoto, Maki; Cole, Patricia; Barret, Olivier; Alagille, David; Papin, Caroline; Morley, Thomas; Fowles, Krista; et al. (European journal of nuclear medicine and molecular imaging, 2022)
Purpose Cholesterol 24-hydroxylase (CH24H) is a brain-specific enzyme that plays a major role in brain cholesterol homeostasis by converting cholesterol into 24 S -hydroxycholesterol. The selective CH24H inhibitor soticlestat (TAK-935) is being pursued as a drug for treatment of seizures in developmental and epileptic encephalopathies. Herein, we describe the successful discovery and the preclinical validation of the novel radiolabeled CH24H ligand (3-[ 18 F]fluoroazetidin-1-yl){1-[4-(4-fluorophenyl)pyrimidin-5-yl]piperidin-4-yl}methanone ([ 18 F]T-008) and its tritiated analog, [ 3 H]T-008. Methods In vitro autoradiography (ARG) studies in the CH24H wild-type (WT) and knockout (KO) mouse brain sections were conducted using [ 3 H]T-008. PET imaging was conducted in two adult rhesus macaques using [ 18 F]T-008. Each macaque received two test–retest baseline scans and a series of two blocking doses of soticlestat administered prior to [ 18 F]T-008 to determine the CH24H enzyme occupancy. PET data were analyzed with Logan graphical analysis using plasma input. A Lassen plot was applied to estimate CH24H enzyme occupancy by soticlestat. Results In ARG studies, binding of [ 3 H]T-008 was specific to CH24H in the mouse brain sections, which was not observed in CH24H KO or in wild-type mice after pretreatment with soticlestat. In rhesus PET studies, the rank order of [ 18 F]T-008 uptake was striatum > cortical regions > cerebellum, which was consistent with CH24H distribution in the brain. Pre-blocking with soticlestat reduced the maximum uptake and increased the washout in all brain regions in a dose-dependent manner. Calculated global occupancy values for soticlestat at a dose of 0.89 mg/kg were 97–98%, indicating maximum occupancy. Conclusion The preclinical in vitro and in vivo evaluation of labeled T-008 demonstrates that [ 18 F]T-008 is suitable for imaging CH24H in the brain and warrants further studies in humans. Graphical abstract